KELAYAKAN FINANSIAL BUDIDAYA RUMPUT LAUT (SEAWEED) METODE RAKIT BAMBU APUNG DI DESA TALANGO KECAMATAN TALANGO KABUPATEN SUMENEP - Fitri, Anis Rhohimatul; agridevina, Isdiantoni; Ekawati, Ida (UPN VETERAN JAWA TIMUR, 2016)
Seaweed is a marine biological resources that have ahigh economic value. Eucheuma cottonii cultivated byfarmers Indonesia since the price is relativelyexpensive and much needed as raw material for localindustry and export. Constraints faced by farmers in thedevelopment of seaweed in the village Talango ie lowproduction, often ice-ice disease causing crop failure.Economic studies need to be done to determine thelevel of seaweed production and incomeof farmers. Itcan provide an overview of the economic position ofseaweed farming. Economic position demonstrates theability of farmers to allocate existing resources and canbe approximated by calculating the feasibility offarming. The purpose of thisstudy was to determinethe production feasibility of seaweed farming. Locationof the study are set intentionally (purposive) in theTalango village of the SumenepDistrict . The analyticalmethod used was the analysis of the feasibility offarming. The results showed that the size of the raft56M² (7m x 8m) total production exceeded the level ofincome-producing plant BEP Rp.108.963,-/raft.Seaweed farming in the Talango village feasible bedeveloped because the level of efficiency of 1.24 andcapital productivity by 24%.Keywords:: Eucheuma cottoni, Production, BusinessFeasibility.